2016
DOI: 10.2172/1236153
|View full text |Cite
|
Sign up to set email alerts
|

Rooftop Solar Photovoltaic Technical Potential in the United States. A Detailed Assessment

Abstract: NREL prints on paper that contains recycled content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
203
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(204 citation statements)
references
References 15 publications
1
203
0
Order By: Relevance
“…Of individual states, 11 As discussed in Gagnon et al (2016), this technical potential is notably greater than a previous NREL estimate (Denholm and Margolis 2008). The difference can be attributed to increases in module power density, improved estimation of building suitability, higher estimates of total number of buildings, and improvements in PV performance simulation tools that previously tended to underestimate productivity.…”
Section: All Buildingsmentioning
confidence: 96%
See 1 more Smart Citation
“…Of individual states, 11 As discussed in Gagnon et al (2016), this technical potential is notably greater than a previous NREL estimate (Denholm and Margolis 2008). The difference can be attributed to increases in module power density, improved estimation of building suitability, higher estimates of total number of buildings, and improvements in PV performance simulation tools that previously tended to underestimate productivity.…”
Section: All Buildingsmentioning
confidence: 96%
“…Gagnon et al (2016) provides a full mathematical description of our modeling, including validation calculations and additional analytical techniques. Here we describe the modeling approach briefly.…”
Section: Rooftop Area and Suitability Modelingmentioning
confidence: 99%
“…NREL has estimated that the solar potential of rooftops amounts to about 39 percent of annual electric sales in 2013 (Gagnon et al. , viii). This is a significant contribution, but not sufficient to power the US electrical grid from solar energy.…”
Section: Land Usementioning
confidence: 99%
“…Studies typically find considerable potential for urban deployment of PV. For example, Gagnon et al calculate that the suitable rooftop space in the state of California can generate 74% of the electricity sold by utilities in 2013, while several New England states are found to be able to generate over 45% of their electricity needs by utilizing existing rooftop area. At the national level, Gagnon et al estimate that rooftop solar power could generate 38.6% of national electricity demand, and similarly, at the city level, cities like Los Angeles (60% of electricity needs), San Francisco (50%), Miami (46%), and Atlanta (41%) show substantial potential .…”
Section: Brief Review Of Recent ‘Solar City’ Assessment Literaturementioning
confidence: 99%
“…For example, Gagnon et al calculate that the suitable rooftop space in the state of California can generate 74% of the electricity sold by utilities in 2013, while several New England states are found to be able to generate over 45% of their electricity needs by utilizing existing rooftop area. At the national level, Gagnon et al estimate that rooftop solar power could generate 38.6% of national electricity demand, and similarly, at the city level, cities like Los Angeles (60% of electricity needs), San Francisco (50%), Miami (46%), and Atlanta (41%) show substantial potential . Gagnon et al performed their calculation for 47 cities across the United States and found that, collectively, these cities have the technical potential to host an impressive 84.4 GW p of solar capacity—the Solar Energy Industry Association (SEIA) puts the current total U.S.‐installed PV capacity at about 25 GW p .…”
Section: Brief Review Of Recent ‘Solar City’ Assessment Literaturementioning
confidence: 99%